Analysis of the temporal and spatial variability of whale shark (Rhincodon typus) aggregation in the South Ari Marine Protected Area, Maldives, Indian Ocean. Issue 1 (1st January 2021) - Valsecchi, S.; Lanfredi, C.; Azzellino, A.; Savini, A.; Bracchi, V. A.; Marchese, F.; Hancock, J.; Rees, R.; Cánovas Pérez, C.
Abstract: Whale sharks are known to aggregate in coastal areas. In the South Ari Marine Protected Area (Maldives) a aggregation, mostly represented by young males with a high level of residency, has been described in the literature. Despite the worldwide interest in the natural resources of the Maldives, this population is increasingly subjected to anthropogenic pressure and major concern regards the flourishing tourist industry. In this study, data collected by the Maldives Whale Shark Research Programme between 2014 and 2017 have been used to detect both temporal and spatial patterns of occurrence. Favourable environmental conditions to visually detect whale sharks have been defined for the studied area. Accordingly, a total of 1077 shark encounters have been analysed in this study. Environmental conditions (i.e. sea surface temperature, monsoon occurrence) have been used to detect possible factors affecting the spatial and temporal variability of Rhincodon typus aggregations. A two-way ANOVA has been performed to detect temporal trends in animal occurrence, sea surface temperature pattern and to investigate the sea bottom depth variability during encounters. Significant differences in the monthly occurrence of whale sharks within the same year and among different years have been detected. Similar patterns have been observed for environmental parameters such as sea surface temperature and depth. A different spatial distribution has also been detected as a function of the Indian Monsoon reversal (north-eastern and south-western) affecting the area. During the northeast monsoon period, whale sharks appeared to concentrate in a smaller longitudinal range closer to the western-central part of the MPA, where deeper water conditions occur due to the proximity of a deep depression (submarine canyon). Results from this study provide new pieces of information for the implementation of dedicated management actions to protect the whale sharks population inhabiting the South Ari Marine Protected Area.